Total Synthesis Establishes the Biosynthetic Pathway to the Naphterpin and Marinone Natural Products. (23rd July 2018) - Murray, Lauren A. M.; McKinnie, Shaun M. K.; Pepper, Henry P.; Erni, Reto; Miles, Zachary D.; Cruickshank, Michelle C.; López‐Pérez, Borja; Moore, Bradley S.; George, Jonathan H.
Abstract: The naphterpins and marinones are naphthoquinone meroterpenoids with an unusual aromatic oxidation pattern that is biosynthesized from 1, 3, 6, 8‐tetrahydroxynaphthalene (THN). We propose that cryptic halogenation of THN derivatives by vanadium‐dependent chloroperoxidase (VCPO) enzymes is key to this biosynthetic pathway, despite the absence of chlorine in these natural products. This speculation inspired a total synthesis to mimic the naphterpin/marinone biosynthetic pathway. In validation of this biogenetic hypothesis, two VCPOs were discovered that interconvert several of the proposed biosynthetic intermediates.